Evaluación de la carga de combustibles forestales en un bosque mixto de la Sierra De Coyuca De Benítez, Estado De Guerrero, México - Naranjo-Esquivel, Erick David (Instituto Tecnológico de Costa Rica, 2014)
The mixed pine-oak forests accumulate dead organic material (necromass) who becomes forest fuel that increases the risk of forest fires promote and represent an important reservoir of forest carbon. Characterization and quantification of forest fuel loads 1 hr, 10 hr, 100 hr firm 1000, 1000 decomposed using the technique planar intersections and loads of litter and organic horizon taking steps deep and dry weight was made calculate the amount of biomass. Four sites with different time after a forest fire (tsf) where plots of 1 ha each site and captured information on the trees and the quantification of fuels were established. The results show an increase in the loads with increasing the time after a forest fire (TFS). The higher load corresponded to reference site (tsf> 40 years) with a total of 55.60 Mg ha-1, the lowest load was presented on the site less tsf with 19.68 Mg ha-1. The highest loading was given by the layer of organic horizon at all sites with up to 69.80% at site 1 and was the only variable that showed significant differences between the four treatments. Carbon captured by necromass in this forest in a total of 364 Mg 156.19, excluding carbon in soils and content in the root system was estimated.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2014.
Keywords: Combustibles; Cuantificación; Caracterización; Análisis; Diversidad; Flora